The early-life fecal microbiota is associated with litter of origin but not with susceptibility to ETEC F4ab-mediated post-weaning diarrhea in CHCF1 genotyped pigs - Martin Peter Rydal; Louise Ladefoged Poulsen; Jens Peter Nielsen (PLoS ONE, 2025)
Introduction Universal biomarkers in the fecal microbiota that predict susceptibility to post-weaning diarrhea (PWD) would be valuable for future intervention strategies. Genetic susceptibility to enterotoxigenic E. coli (ETEC) infection in pigs is a major determinant of PWD and may unfavourably alter early-life gut microbiota composition. We investigated whether pigs genetically susceptible to ETEC F4ab/ac had different fecal microbiota composition and diversity pre- and post-weaning compared to genetically resistant pigs. Method Fecal microbiotas were characterized using long-read sequencing of the 16S rRNA gene in 24 CHCF1 heterozygous susceptible (RS) and 24 CHCF1 homozygous resistant (RR) pigs. These pigs were tested at early lactation (post-natal day (PND) 8) and late lactation (PND 22), which are critical periods for microbiota development and immune maturation. Twelve pigs from each group were weaned and transported to an experimental facility at PND 23, and were tested again at PND 24, prior to an ETEC F4ab challenge. This enabled studying immediate fecal microbiota changes after weaning and investigating whether CHCF1 RS pigs had compromised microbiotas compared to CHCF1 RR pigs preceding infection. Results Across time, CHCF1 RS pigs had a higher number of observed OTUs (coef: 103, 95% CI [18.90; 192.76], p = 0.01) compared to CHCF1 RR pigs. There were no significant differences in the overall bacterial communities or differentially abundant taxa between genotypes. Littermates had bacterial communities more similar to each other compared to non-littermates during lactation (PND 8: R2 = 0.2, p = 0.001 and PND 22: R2 = 0.23, p = 0.001) and the litter effect persisted after weaning (PND 24: R2 = 0.4, p = 0.001). Conclusion We did not find major differences in the fecal microbiota between CHCF1 genotypes, pre- or post-weaning, that could help explain subsequent susceptibility to ETEC F4ab-mediated PWD. Litter explained a major part of the variation in the overall fecal bacterial community between pigs in the study.